Switchable platinum-based tweezers with Pt–Pt bonding and selective luminescence quenching1. Issue 18 (14th May 2015) - Doistau, Benjamin; Rossi-Gendron, Caroline; Tron, Arnaud; McClenaghan, Nathan D.; Chamoreau, Lise-Marie; Hasenknopf, Bernold; Vives, Guillaume
<x xml:space="preserve">Abstract</x> Molecular tweezers incorporating peripheral platinum salphen complexes and a central chelating terpyridine group have been synthesized and their switching and photophysical response to metal ions studied.